Analyzing the Key Drivers of E-Commerce Adoption in MSMEs: an Empirical Research in Indonesia - Harsasi, Meirani; Andi Mulyana; Mutmainah, Isbandriyati; Aprihatiningrum Hidayati; Erni Ernawati; Ahsla Nauli Dinanti Sianipar (Apollo: Journal of Tourism and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, significantly contributing to the Gross Domestic Product (GDP). However, the shift in consumer behavior from traditional shopping to online shopping necessitates MSMEs to adapt to information technology, particularly e-commerce. This study aims to identify the factors supporting e-commerce adoption by MSMEs, including competitive pressure, entrepreneurial mindset, perceived benefits, and owner/HR knowledge. This research employs a quantitative approach using Partial Least Square (PLS) methods to analyze data from 358 MSMEs respondents in Bandung, Yogyakarta, Denpasar, and Mataram. The results indicate that all independent variables (competitive pressure, entrepreneurial mindset, perceived benefits, and knowledge) significantly influence e-commerce adoption. These findings provide practical contributions for SMEs in developing effective e-commerce adoption strategies.